Stilles Land - Stieler, Laila 1965-; Höfer, Andreas 1964-; Merten, Thorsten 1963-; Arndt, Jeannette 1970-; Böwe, Kurt 1929-2000 (Filmgalerie 451, 2007)
The German Democratic Republic autumn 1989. A provinical theatre is planning to stage Samuel Beckett's 'Waiting for Godot'. Political events - the exodus of East-Germans via the Hungarian border, the revolution, the fall of the wall - overshadow the rehearsals.
Bildformat 1.66:1
Orig.: Deutschland 1992
Enth. 6 Kurzfilme: Konsequenzen - Peter (1987). Was jeder muss ... (1988). Nachts schlafen die Ratten (1988). Jenseits von Klein Wanzleben (1989). Zug in die Ferne (1989). So schnell es geht nach Istanbul (1990)
Enth.: Konsequenzen - Peter , 25. - Was jeder muss ... - Nachts schlafen die Ratten. - Jenseits von Klein Wanzleben. - Zug in die Ferne. - So schnell es geht nach Istanbul
Enth. Interview ; Making-Of "Stilles Land" ; Filmographie mit Kinotrailern ; Presseschau
Keywords: Geschichte; Germany (East) -- History -- 1989- -- Drama